Research on hillslope processes in Costa Rica, Honduras, Mexico and Nicaragua: teachings from the academy, cooperation agencies and public institutions - Quesada-Román, Adolfo; Moncada-López,, Rigoberto; Paz-Tenorio, Jorge Antonio; Espinoza-Jaime, Eveling; Gutiérrez-Gutiérrez, Carmen; Castellón-Meyrat, Alex; Acosta-Galeano,, Norwin (Revista Geográfica de América Central., 2018)
This paper specifies the range of products from which specialists from Costa Rica, Honduras, Mexico and Nicaragua develop cartography on hillslope movements, an aspect that can illustrate the accessibility to certain data, as well as the scarcity or lack of specific information in the region. Works carried out from Government Institutions, Cooperation Agencies and the Academy try to join forces with national authorities at each place in the study of this phenomenon. The terminology used in each project is respected, and the term hillside movements is considered equivalent. This mapping is intended to be a baseline input for studies on Disaster Risk Management and Land Use Planning in cities, basins and municipalities throughout Latin America.